RhoGEF17: an essential regulator of endothelial cell death and growth - Weber, Pamina; Baltus, Doris; Jatho, Aline; Drews, Oliver; Zelarayan, Laura C.; Wieland, Thomas; Lutz, Susanne (Cells, 2021)
The Rho guanine nucleotide exchange factor RhoGEF17 was described to reside in adherens junctions (AJ) in endothelial cells (EC) and to play a critical role in the regulation of cell adhesion and barrier function. The purpose of this study was to analyze signal cascades and processes occurring subsequent to AJ disruption induced by RhoGEF17 knockdown. Primary human and immortalized rat EC were used to demonstrate that an adenoviral-mediated knockdown of RhoGEF17 resulted in cell rounding and an impairment in spheroid formation due to an enhanced proteasomal degradation of AJ components. In contrast, β-catenin degradation was impaired, which resulted in an induction of the β-catenin-target genes cyclin D1 and survivin. RhoGEF17 depletion additionally inhibited cell adhesion and sheet migration. The RhoGEF17 knockdown prevented the cells with impeded cell-cell and cell-matrix contacts from apoptosis, which was in line with a reduction in pro-caspase 3 expression and an increase in Akt phosphorylation. Nevertheless, the cells were not able to proliferate as a cell cycle block occurred. In summary, we demonstrate that a loss of RhoGEF17 disturbs cell-cell and cell-substrate interaction in EC. Moreover, it prevents the EC from cell death and blocks cell proliferation. Non-canonical β-catenin signaling and Akt activation could be identified as a potential mechanism.